Konsep Asesmen Ranah Kognitif dalam Pendidikan - Ranti Karmila; Dina Fitria Handayani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Cognitive domain assessment is an important component in the learning process which aims to measure students' mastery of knowledge and thinking abilities. This research presents the concepts, principles and implementation of cognitive assessment in education through literature studies. Bloom's Taxonomy revised by Anderson and Krathwohl divides the cognitive domain into six levels: remembering, understanding, applying, analyzing, analyzing, and creating. Developing an effective cognitive assessment instrument requires systematic planning, starting from determining objectives to analyzing question items. Various assessment techniques such as multiple choice tests, short content, descriptions, and true and false can be used according to learning objectives. Challenges in implementing cognitive assessments include difficulties in designing instruments that measure higher-order thinking abilities. A deep understanding of the principles and techniques of cognitive assessment is essential for educators to improve the quality of learning and assessment.